2010
DOI: 10.5380/re.v36i1.22994
|View full text |Cite
|
Sign up to set email alerts
|

Teoria da estabilidade do equilíbrio competitivo em mercado múltiplo numa economia Arrow & Debreu

Abstract: Este artigo tem por objetivo expor o debate contemporâneo sobre ascontribuições principais à teoria da estabilidade do equilíbrio competitivo emuma economia submetida a processos diversos de ajustamento: Tâtonnement eNonTâtonnement. Discutimos os principais resultados estabelecidos pelos autorespertinentes a literatura sobre a teoria da estabilidade do equilíbrio walrasiano.Enunciamos e discutimos alguns dos principais teoremas. E primando pela didáticarealizamos exemplos numéricos, quando pertinentes, alguns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…For instance, we observed that mule foals (n = 30) have a higher APGAR score when compared to equine neonates (n = 17) immediately after birth and 60 min after birth [4], which can be related to differences in progestogen clearance in the neonatal period. The popularity of mules has grown in recent years with their increasing use in competitive sporting events including roping, gaited competitions and trail rides [5,6]. Thus, the demand for healthy mule foals, with superior genetics has resulted in an increase in breeding them.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, we observed that mule foals (n = 30) have a higher APGAR score when compared to equine neonates (n = 17) immediately after birth and 60 min after birth [4], which can be related to differences in progestogen clearance in the neonatal period. The popularity of mules has grown in recent years with their increasing use in competitive sporting events including roping, gaited competitions and trail rides [5,6]. Thus, the demand for healthy mule foals, with superior genetics has resulted in an increase in breeding them.…”
Section: Introductionmentioning
confidence: 99%